Phenomenological study of primiparous mother's experience of emergency cesarean section in Yogyakarta - Ratna Widhiastuti; Detty Siti Nurdiati; Wahyu Ikka setyarini (Berita Kedokteran Masyarakat (BKM), 2016)
PurposeThe purpose of the study was to explore the experience of primipara mother when the emergency cesarean section was decided at RSUD Wates Kulon Progo Yogyakarta.MethodA phenomenological study was conducted involving indepth interview of 7 post emergency cesarean section mothers at Wates Kulon Progo Yogyakarta hospital in April-July 2014.ResultsThe study found three themes on the mother experience related to emergency cesarean section; the perception of the mother associated with emergency cesarean section, the influence of spirituality on positive perceptions of mothers and support for mothers in the face of emergency cesarean section.ConclusionMothers have a specific strategy in dealing with the emergency cesarean section which they will experience. Support for mothers in facing emergency cesarean section, spirituality influence on mother's positive perception and mother perception related to emergency cesarean section affects mother's readiness to undergo emergency cesaeran section. It is necessary to create a policy focusing on FCMC by involving family counselors when the mother is determined by emergency cesarean section.